Conservation of Cultural Tourism in the Perspective of the Pentahelix Model - Amin; Supriyatno, Yanto; Nuraini, Siti; Fadil, Muhammad (International Journal of Science and Society, 2025)
This study aims to answer the question of how each actor of the pentahelix model plays a role in the conservation of cultural tourism in the Betawi Setu Babakan Village, Jakarta, according to research that has been conducted. The research method used is a systematic literature review (SLR), a method that aims to systematically identify, study, evaluate and interpret data in journals according to the steps that have been set. Based on these stages, four journal articles were selected, namely: analysis of the potential of the Betawi Setu Babakan Cultural Village in the development of sustainable tourism objects; SWOT analysis as an effort to improve tourism planning capabilities through the 5A approach to tourism potential in the Betawi Setu Babakan Cultural Village; development of the Betawi Setu Babakan Cultural Village as a cultural tourism area in Jakarta; and planning and development of resources for the tourism industry in the Betawi Setu Babakan Cultural Village, Serengseng Sawah Jagakarsa, South Jakarta, DKI Jakarta Province. The results of the study show that apart from academic actors, the five pentahelix actors, namely business, government, community, and media, have not played an optimal role, so there is still a lot of homework to be done.